Aplikasi Seven Tools pada Perbaikan Mutu Roundness Bakso Unyil di PT X - Muhandri, Tjahja; Pratama, Andika Putra; Hunaefi, Dase (Institut Pertanian Bogor, 2019)
The roundness quality of small meatballs, called Bakso Unyil, produced by PT X has been considered non-uniform and in-competitive. Hence, roundness quality improvement has been becoming one of the priorities for increasing consumer acceptance. This research aims to identify the causes of the poor quality of Unyil Meatballs roundness and find a solution. The improvement methods were: identification of the causes of low quality of roundness (Plan), improvement trials based on alternative solution (Do), and implementation of corrective actions (Action). A total of 60 meatballs samples were taken from three batches (for each batch of 20 samples). Ishikawa Diagram, and histogram were conducted and analysed. Implementation of alternative solutions to improve roundness quality that have been carried out as follows: 1). adjusting the amount of dough in mixing step, 2). the installation of temperature measuring equipment in the preheater, 3). Usage standardization of ice, 4). improvement of phosphate and salt mixing techniques, 5). removal of baking powder, and 6). turn of blades in mixing cake. Result showed that those improvements were not only improve the roundness quality of Unyil meatballs but also improve the smoothness and reducing wrinkle conditions on the surface of Unyil meatballs